2011
DOI: 10.21273/horttech.21.5.525
|View full text |Cite
|
Sign up to set email alerts
|

Brassicaceae Cover Crops Affect Seed Germination and Seedling Establishment in Cucurbit Crops

Abstract: Field and laboratory bioassay studies were conducted to determine the impact of Brassicaceae cover crops on cucurbit germination percentages and stand counts. A 2-year field study in southwestern Michigan examined the effect of oilseed radish (Raphanus sativus var. oleiferus), oriental mustard (Brassica juncea), and yellow mustard (Sinapis alba) green manures on muskmelon (Cucumis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
11
2
Order By: Relevance
“…When planted at the optimal date in the fall, mustard biomass was about 4 t ha −1 , whereas the typical range from spring plantings was from 2 to 4 t ha −1 . While some studies have found a similar range in mustard biomass in northcentral and northeastern United States (Stivers‐Young, 1998; Haramoto and Gallandt, 2005a; Ackroyd and Ngouajio, 2011), spring mustard biomass has been found to reach as high as 6.8 t ha −1 (Kumar et al, 2009). In both New York and Michigan, fall mustard biomass was generally greater with earlier planting dates, largely due to greater GDD accumulation.…”
Section: Discussionmentioning
confidence: 95%
“…When planted at the optimal date in the fall, mustard biomass was about 4 t ha −1 , whereas the typical range from spring plantings was from 2 to 4 t ha −1 . While some studies have found a similar range in mustard biomass in northcentral and northeastern United States (Stivers‐Young, 1998; Haramoto and Gallandt, 2005a; Ackroyd and Ngouajio, 2011), spring mustard biomass has been found to reach as high as 6.8 t ha −1 (Kumar et al, 2009). In both New York and Michigan, fall mustard biomass was generally greater with earlier planting dates, largely due to greater GDD accumulation.…”
Section: Discussionmentioning
confidence: 95%
“…Brassicaceae oilseed meals represent a particular type of meals; despite the similar N and phosphorous (P) content with respect to sunflower, no genetically improved seeds contain glucosinolates (GLSs) that through enzymatic hydrolysis via myrosinase produce a series of biologically active compounds (mainly isothiocyanates) (Fahey et al, 2001) that have shown an effect in controlling weeds (Ascard and Jonasson, 1991;Vaughn and Berhow, 1998;Vaughn et al, 2006;Rice et al, 2007), insect pests (Elberson et al, 1996(Elberson et al, , 1997, nematodes (Walker, 1996;Lazzeri et al, 2009), and soilborn pathogens (Smolinska et al, 1997;Manici et al, 1997;Mazzola et al, 2001;Chung et al, 2002). On the other hand, some authors demonstrated also significant allelopathic effects on seedlings of crops seeded after soil incorporation of brassicaceous crops with high GLS content (Jafariehyazdi and Javidfar, 2011), whilst for transplant crops, such as field vegetables, only minor effects on plant growth are reported (Haramoto and Gallandt, 2004;Ackroyd and Ngouajio, 2011). In any case the biocidal activity was clearly related to GLSs-type and concentration Vaughn, 1999;Bending and Lincoln, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to identifying and establishing a suitable cover crop, another factor to consider is the planting date of the vegetable crop soon after termination of the cover crop. Ackroyd and Ngouajio (2011) suggested that planting too soon after cover crop termination decreased muskmelon yield (Cucumis melo) when using oilseed radish, oriental mustard (Brassica juncea), and yellow mustard (Sinapis alba). Certain cover crops have also been shown to decrease vegetable yield.…”
Section: Dedicationmentioning
confidence: 99%
“…Little research has been done regarding the planting date of vegetable transplants after a cover crop has been terminated (Ngouajio, 2011) especially with the cover crops selected for this study. One reason to consider this parameter is the presence of allelotoxins from the cover crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation